Implementation of Building Information Modelling Training to Strengthen Design-Building Competencies of Vocational Teachers and Students - Zulfikar, Ahmad; Wijaya, Kinanti; Sutrisno,; Wibowo, Harry; Nasution, Rafika Hilmi; Lokantara, I Gede Wyana; Arjuna, Fajar; Harun, M. Andrey; Nduru, Jun Kristiani; Siburian, Natachia; Daulay, Nabilah Fernanda; Putra, Riansyah; et al. (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve the Building Information Modeling (BIM) competencies of vocational teachers and students at SMKN 1 Lubuk Pakam and to support the integration of BIM into vocational building design education. The program was implemented through demonstrations, hands-on training, and curriculum integration assistance. A total of 16 participants, consisting of teachers and students from the Building Modeling and Information Design program, took part in the activities. Data were collected using a BIM knowledge test, a perception questionnaire, a teacher readiness questionnaire, and a practical assessment rubric for BIM modeling skills. Descriptive statistics were used to summarize the data, while changes in participants' BIM knowledge were analyzed using the Wilcoxon signed-rank test. The results showed that the mean BIM knowledge score increased from 17.62 on the pre-test to 19.88 on the post-test. This improvement was statistically significant (p = 0.039), with a moderate effect size (0.65). Participants' perceptions of BIM also improved, with the mean score increasing from 3.44 to 4.09 and the proportion of responses in the high category rising from 51.3% to 90.0%. Teachers' readiness to integrate BIM into classroom instruction increased substantially, with the mean score rising from 2.00 to 4.36 and the proportion of high-category responses increasing from 13.9% to 94.0%. In addition, participants successfully applied fundamental BIM workflows and produced simple digital building models. These findings indicate that the program effectively enhanced participants' BIM knowledge, practical competencies, and teachers' readiness to integrate BIM into vocational learning. Nevertheless, sustained mentoring and advanced training are recommended to support the development of more complex BIM competencies and long-term curriculum implementation.